Re-introducing politics in african farmer-led irrigation development : introduction to a special issue - (:unkn) unknown (My University, 2019)
This introduction is a reflexive piece on the notion of farmer-led irrigation development and its politics. It highlights the way the varied contributions to the Special Issue support a shared perspective on farmer-led irrigation development as a process whereby farmers drive the establishment, improvement, and/or expansion of irrigated agriculture, often in interaction with other actors. We analyse how the terminology is used and reproduced, and what it means for our understanding of irrigation policy and practices in sub-Saharan Africa. A central tenet of our argument is that farmer-led irrigation development is inherently political, as it questions the primacy of engineering and other expert knowledges regarding the development of agricultural water use practices in Africa as well as the privileging of formal state planning or technical solutions. We show how mainstream understanding of farmers' engagement focuses on (1) regulation and control, (2) profitability, and (3) technical efficiency. We demonstrate how these three perspectives have contributed to depoliticised readings of farmer-led irrigation (development), which has been essential to the ability of the terminology to travel and find global allies. Second, we explore the paradox of the invisibility of farmer-led irrigation development in national policies and practices. We discuss practical and political reasons underlying this silence and point out that there are important advantages for irrigators in not being visible. In conclusion we highlight what can be gained from adopting an explicitly political analysis of the processes through which farmers engage in irrigation on their own terms.
Keywords: African Research